A Case of Neurotoxic Snake Bite in a Metropolitan City (New Delhi): Pain Abdomen with Anaphylaxis as a Presentation - Virmani, Shruti; Yadav, Avanish Kumar (Indian Journal of Case Reports, 2017)
Snake bites present as life threatening emergencies and are seen more commonly in rural tropical countries. Snake bites have neurotoxic, hemotoxic, myotoxic or mixed presentation. We present a case of neurotoxic snake bite in an urban setting of New Delhi, a metropolitan city, where snake bites aren’t common. The patient presented as an acute emergency in casualty, without any previous forthcoming history of snake bite, with a history of pain abdomen, vomiting and signs of anaphylaxis. Rapidly progressive neurological deficit started with ptosis followed by stridor, dyspnoea, respiratory arrest and shock. The patient was given standard management of anaphylaxis and snakebite (polyvalent anti-snake venom and neostigmine) based on WHO guidelines of snake bite. Patient recovered without any neurological deficit within a week. Although snakebites are rare in urban setting, they are reported. Neurotoxic snakebites can occur in sleep by kraits and can present as catastrophic life threatening emergency in early morning hours, as in our case.